Telomere Length and Oxidative Damage in Children and Adolescents with Autism Spectrum Disorder: A Systematic Review and Meta-Analysis - Leping Ma; Cui Liu; Ran Song; Yeping Qian; Feng Zhang (Journal of Integrative Neuroscience)
Background: Autism spectrum disorder (ASD) has been reported to confer an increased risk of natural premature death. Telomere erosion caused by oxidative stress is a common consequence in age-related diseases. However, whether telomere length (TL) and oxidative indicators are significantly changed in ASD patients compared with controls remains controversial. The aim of this study was to determine the associations of ASD with TL and oxidative indicators by performing a meta-analysis of all published evidence. Methods: The PubMed and Embase databases were searched for articles published up to April, 2024. The effect size was expressed as standardized mean difference (SMD) and 95% confidence interval (CI) via Stata 15.0 software. Results: Thirty-nine studies were included. Pooled results showed that compared with controls, children and adolescents with ASD were associated with significantly shorter TL (SMD = –0.48; 95% CI = –0.66– –0.29; p < 0.001; particularly in males), lower total antioxidant capacity (TAC: SMD = –1.15; 95% CI = –2.01– –0.30; p = 0.008), and higher oxidative DNA (8-hydroxy-2′-deoxyguanosine, 8-OHdG: SMD = 0.63; 95% CI = 0.03–1.23; p = 0.039), lipid (hexanolyl-lysine, HEL: SMD = 0.37; 95% CI = 0.13–0.62; p = 0.003), and protein (3-nitrotyrosine, 3-NT: SMD = 0.86; 95% CI = 0.21–1.51; p = 0.01; dityrosine, DT: SMD = 0.66; 95% CI = 0.521–0.80; p < 0.01) damage. There were no significant differences between ASD and controls in 8-isoprostane and oxidative stress index after publication bias correction, and in N-formylkynurenine during overall meta-analysis. Conclusions: TL, 8-OHdG, TAC, HEL, 3-NT, and DT represent potential biomarkers for prediction of ASD in children and adolescents.